MG-125 CYP21A2 mutation spectrum in congenital adrenal hyperplasia identified from molecular genetic testing. (4th December 2015) - Xi, Yanwei; Parboosingh, Jillian; Johnson, Heather; Graham, Lisa; Lamont, Ryan
Abstract : Background: Mutations in CYP21A2, the gene encoding 21-hydroxylase, are identified in >80% of individuals with congenital adrenal hyperplasia (CAH). CYP21A2 and its highly homologous pseudogene, CYP21A1P, reside in close proximity; as a result >90% of CYP21A2 mutation-containing alleles are caused by gene conversion from CYP21A1P or CYP21A2 deletions arising from non-allelic homologous recombination. Further, CYP21A2 duplications exist and provide a source of false negative and false positive results as carriers of a CYP21A2 deletion may be masked by a CYP21A2 duplication on the opposite allele (2+0 configuration) or carriers of a point mutation may also carry a second non-mutated CYP21A2 in cis. Objectives: The purpose of this study was to investigate the distribution of CYP21A2 mutations identified from molecular genetic tested CAH individuals and determine the frequency of 2+0 carriers in a control population. Methods: A total of 469 CAH individuals were screened for CYP21A2 mutation by MLPA and common mutation and/or sequencing analysis. A PCR-based assay was developed and to detect 2+0 CYP21A2 deletion carriers. Results: The p. V282L, c.293–13A/C >G, and CYP21A2 gene deletion were the most frequent mutations identified in CAH. Cases with two independent mutations in cis and mutation-containing CYP21A2 duplications were observed. No silent 2+0 CYP21A2 deletion carriers were identified in our control population. Conclusions: Segregation and copy number analysis are critical in CYP21A2 testing. A PCR-based assay can be used to detect CYP21A2 duplications, although the 2+0 silent carrier frequency is rare.